Eliciting Information From Multiple Experts - Asher Wolinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
A decision maker has to elicit information from informed experts regarding the desirability of a certain action from experts who share similar preferences which differ significantly from those of the decision maker. The question is how much information the decision maker can elicit, despite the difference in interests. The focus here is on ways in which the decision maker can take advantage of the multiplicity of experts. if the decision maker cannot commit to a mechanism and there is no communication among the experts, then no useful information is elicited from the experts in the equilibrium. If the experts can be partitioned into groups such that the members of each group can communicate with each other before they report their information to the decision maker, then more information can be elicited. Obviously, if all experts are allowed to communicate, they can be induced to reveal the relevant information, at least, when their aggregate information makes it desirable for them to undertake the project. The more interesting observation is that, if communication among the experts can be restricted to certain subsets, then even more information can be elicited. Finally, if the decision maker can commit to a mechanism, the information elicited in some cases is sufficient to implement the decision maker's best outcome in all but one state. All these observation make straightforward use of the idea that experts choose their report with the understanding that it matters only when they are pivotal.
Keywords: 330